М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
bissimbayevaa
bissimbayevaa
27.05.2021 03:38 •  Алгебра

Y=2x-3 найти y(2),y(0.3).y(0),y(-6) найти x если y=0; -2; 5

👇
Ответ:
адевале1
адевале1
27.05.2021
Y(2) = 2*2 - 3 = 4 - 3 = 1 
y(0.3) = 2*0.3 - 3 = - 2.4
y(0) = 2*0 - 3 = - 3
y( - 6) = - 2*6 - 3 = - 15

2x - 3 = 0 
2x = 3 
x = 1,5

2x - 3 = - 2
2x = 1
x = 0,5

2x - 3 = 5
2x = 8
x = 4 
4,6(52 оценок)
Открыть все ответы
Ответ:
BazikPro
BazikPro
27.05.2021

x_{1} = -3 + \sqrt{6}           x_{2} = -3 - \sqrt{6}           x_{3} = 1                x_{4} = -7

Объяснение:

(x² + 6x)² - 4(x² + 6x + 1) - 17 = 0

t = (x² + 6x)

t² - 4(t + 1) - 17 = 0

t² - 4t - 4 - 17 = 0

t² - 4t - 21 = 0

t² + 3t - 7t - 4 - 17 = 0 (Теорема Виета)

t² + 3t - 7t - 21 = 0

t(t + 3) - 7(t + 3) = 0

(t + 3)(t - 7) = 0

t₁ = -3; t₂ = 7

x² + 6x + 3= 0                                           x² + 6x - 7 = 0

D = b² - 4ac                                              D = b² - 4ac

D = 6² - 4 * 1 * 3                                        D = 6² - 4 * 1 * (-7)

D = 36 - 12                                                D = 36 + 28

D = 24                                                       D = 64

x_{1,2} = \frac{-b +- \sqrt{D} }{2a}                                           x_{3,4} = \frac{-b +- \sqrt{D} }{2a}

x_{1,2} = \frac{-6 +- \sqrt{24} }{2 * 1}                                          x_{3,4} = \frac{-6 +- \sqrt{64} }{2 * 1}

x_{1,2} = \frac{-6 +- 2\sqrt{6} }{2}                                          x_{3,4} = \frac{-6 +- 8 }{2}

x_{1} = \frac{2(-3 + \sqrt{6)} }{2}           x_{2} = \frac{2(-3 - \sqrt{6)} }{2}          x_{3} = \frac{2 }{2}               x_{4} = \frac{-14}{2}

x_{1} = -3 + \sqrt{6}           x_{2} = -3 - \sqrt{6}           x_{3} = 1                x_{4} = -7

4,5(46 оценок)
Ответ:
tatite15
tatite15
27.05.2021

Диалог 1.

Jim: Here`s my present. I hope you like it.

Billy: That`s very kind of you! I`v always wanted cap like this!

Jim: I`m glad you like this. Try it on and see if it fits.

Billy: I think this is coll. What do you think?

Jim: It matches the colour of your T-shirt. I`m glad you liked it.

Диалог 2.

Jim: This is for you.

Shelley: That`s very kind of you! What is it?

Jim: Open it and see.

Shelley: Wow. It`s a lovely skirt.

Jim: I`m glad you like this. Are they your size?

Shelley: Oh, no. They're too big.

Jim: That`s all right. You can exchange them.

Shelley: Thanks

Jim: Don`t mention it.

Вроде так, если каждый диалог нужна была новая вещь. Если я не правильно поняло, то можно просто слово поменять.

4,7(12 оценок)
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ